Proximate and Nutritional Composition of Stored Bulb Onions as Affected by Harvest and Postharvest Treatments - Irene N. Kiura; Bernard M. Gichimu; Felix Rotich (International Journal of Agronomy)
Productivity of bulb onions (Allium cepa L.) is largely constrained by postharvest losses. There are several postharvest strategies applicable to onions, but they are mostly applied singularly and therefore their combined effects have not been well studied. This study was set out to evaluate the effects of harvesting stage, curing period, and time of topping on postharvest quality of stored red bulb onions. The study was carried out in Yatta Subcounty, Machakos County, Kenya. The experimental design was split-split plot laid out in a 3 × 3 × 2 factorial arrangement. The treatments consisted of harvesting stage (25%, 50%, and 75% top fall), curing period (none, 1 week, and 2 weeks after harvesting), and time of topping (before and after curing). All the treatments were replicated three times. After 3 months of storage, the bulbs were analyzed for proximate and nutritional composition. Bulbs that were harvested at 75% top fall and cured for one or two weeks before topping retained higher moisture content, bulb weight, crude protein, vitamin C, zinc, potassium, calcium, and iron but lower sodium content after three-month storage. These practices are therefore recommended for maintaining the nutritional quality of bulb onions after harvesting.